Kerk en samelewing in die dokumente “Kerk en samelewing” na 25 jaar - Strauss, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Church and society in the documents Church and society after 25 years The first document called “Church and society” (CS) of the Dutch Reformed Church was accepted 25 years ago by the General Synod of that year. The next General Synod, that of 1990, revised CS without changing its direction or the meaning of it’s content. The main aim of CS was to take a new stance in the Dutch Reformed Churchon apartheid. CS not only denounced any Biblical support for apartheid, it also came out against the way in which it functioned in Southern Africa. This article investigates what CS holds for the Dutch Reformed Church after 25 years. Two matters are looked into: the content of CS as well as how it functioned as a church prophet in the last years of official apartheid.